Method of accounting and approaches to tax optimization of income tax of entities - V.V. Sokolovska (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article focuses on the organization and methodology of income tax accounting. It describes the documented operations related to the calculation and payment of income tax and it suggests the standard form of the original document to reduce the time for calculation of tax and facilitation in filling in the tax return. The author describes the accounts system designed for income tax cost accounting, and gives their analytical sections. The article discloses the need of management reports for this tax and suggests to implement the standard form of report for an enterprise for the efficiency of management of revenues, costs, and as a result, income tax. The author singles out the methods of tax optimization of income tax calculation base in the following four areas: the methods related to the fixed assets of the enterprise, inventory, accounts receivable, and the employee's salary. The algorithm of the tax optimization in enterprises is developed. This algorithm, due to the simplicity of its shape, will help management personnel and an accountant of an enterprise to identify possible ways of reducing the amounts payable for income tax under the current legislation.